Analysis of aerodynamic characteristics of missile with different sweep angle under supersonic condition. Issue 4 (March 2021) - Yi, Lin; Li, Yu; Ma, Liangzheng; Ao, Yuntu; Wang, Ying
Abstract: The increasing complexity of the modern battlefield requires that the aircraft can achieve multi-mission and low energy operation. In this paper, the dynamic characteristics of the missile are analyzed by building a 3D model of the missile and CFD simulation, in order to study the dynamic characteristics of the missile at different swept back angles. The lift force and drag force of the missile under different sweeps are studied, and the influence of the variable sweep angle on the aerodynamic characteristics of the whole body is revealed.